STUDI KESIAPAN MAGANG INDUSTRI (MI) MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN FKIP UNS - Ngatou Rohman; Herman Saputro (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The FKIP UNS Mechanical Engineering Education study program is one of the clusters in vocational education that produces vocational teacher candidates. To equip the competencies required to become a SMK teacher in the field of Mechanical Engineering and Automotive Engineering, it is necessary to gain experience in the industry. Industrial Internship is one of the subjects that must be taken by students of the Mechanical Engineering Education Study Program FKIP UNS as a graduation requirement. To examine the extent to which students carry out industrial apprenticeship programs in terms of the aspects of students and study programs, it is necessary to conduct research on the analysis of Industrial Internship readiness of students of the Mechanical Engineering Education Study Program FKIP UNS which can then be used as a basis for making policies regarding industrial apprenticeships. The design in this research is descriptive quantitative. The data collection technique was carried out in a survey using a questionnaire. The respondents in this study were all students of the Mechanical Engineering Education Study Program FKIP UNS class of 2020 or semester IV who will carry out the Industrial Internship program in 2022. The research data were analyzed descriptively with the help of the SPSS program. The results showed that 1) the readiness for industrial internships for students of the Mechanical Engineering Education Study Program FKIP UNS class of 2020 was 3.93 which was in the good category. 2) in providing industrial apprenticeship services for students, the Mechanical Engineering Education study program FKIP UNS makes an industrial apprentice manual and appoints an industrial apprentice coordinator.